International Justice and Pancasila: A Case Study of The Gambia - Mendy, Ousu (Fakultas Hukum Universitas Lampung, 2024)
International justice is as topical as it is relevant to global governance. This is manifest in fledgling and thriving democracies, failed and enduring states, and tyrannous and constitutionally governed states. Similar to the Gambian transitional justice, the Pancasila’s social justice system in Indonesia also depicts an unfulfilled project of promoting justice and order during the transition period. Therefore, to make a comprehensive study of international justice and Pancasila using The Gambia as a case study, normative legal research is adopted through a conceptual framework of the international justice and its relation to Pancasila and The Gambia. It focuses on investigating the relation between international justice, Pancasila justice, and the justice system of The Gambia. Both Indonesia and The Gambia experience authoritarianism for decades and they are undergoing democratisation, but the political interests of their post-authoritarian governments over national interests mar their transitional justice systems. Thus, this research, recommends that prioritisation of victim participation, ensuring comprehensive mechanisms like truth and reparations commissions, putting into effect institutional reforms to prevent future abuses, advancing broad public engagement, addressing foundational causes of conflicts, and connecting efforts with other peacebuilding initiatives are keys to a successful transitional justice system.